Pengaruh Komunikasi, Disiplin, Pengembangan Karir, dan Motivasi Kerja terhadap Kinerja Karyawan PT XYZ - Ranisah, Fitria; Oktiani, Friska; Rutmaya, Rutmaya; Sumbogo, Ignatius Ario (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
This study aims to determine the effect of communication, discipline, career development, and work motivation on employee performance at PT XYZ. This study uses a field research method with a quantitative approach. This research was conducted by the employee analyst unit of PT XYZ, with a population of 51 employees. The sampling method used is Non-Probablity sampling with saturated sampling with a total of 51 employees with data collection techniques using path analysis using SPSS version 25. The results of this study conclude that there is a positive and significant effect of communication on employee performance, there is a negative effect of Discipline on Employee Performance, there is a positive and significant effect of Career Development on Employee Performance, there is a positive and significant influence of Work Motivation on Employee Performance and simultaneously Communication, Discipline, Career Development, and Work Motivation have an influence on Employee Performance of PT XYZ.